SUPERIORITAS BUDAYA ASING DI INSTITUT TEKNOLOGI BANDUNG - Naqisya Arifani; Muhammad Duta Wibawa Mawardi; Fiona Angelica Tjahjono; Elizabeth Michele; Maynardo Pratama Soegianto; Fathimah Afra Nailah Adma; Shelly Delfiani; Amelia Rahma Putri; Jesslyn Gracsella Rusli; Fedora Yoshuara; Jeremy Jeremy; Christian August; Tarissa Cindy Fitrian (Universitas Lancang Kuning, 2022)
Xenocentrism is a phenomenon that has recently been embedded in people's lives, especially students, where they feel a culture-based tendency to value other cultures more than their own, which can manifest in various ways. In practice, xenocentrism can indirectly pose a threat to the identity and national integrity of the Indonesian nation. Therefore, this study was conducted to show the superiority of foreign cultures within the scope of the observed ITB students and how the decline of nationalism was seen from the implementation of foreign cultures within the scope of ITB students. The research method used in this research is descriptive research. The sample used is the students of the Bandung Institute of Technology with a total of 247 respondents. The respondent sampling method used is the method of convenience samples or accidental samples and also purposive. The benefit of this research is to build awareness of ITB students on the importance of respecting the nation's culture and fostering national integrity in the lives of ITB students. The results showed that the level of xenocentrism in ITB was not too high, although overall the level of xenocentrism in Indonesia was quite high.